PENERAPAN MODEL PEMBELAJARAN PROJECT-BASED LEARNING PADA MATA PELAJARAN CNC DENGAN BANTUAN APLIKASI CNC SIMULATOR UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XI SMKN 3 SURABAYA - Aryya Deva Firdauz Attarix; Sita Jihan Fadilah; Alfian Dwi Cahyo; I Made Arsana; Dwi Wulandiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was conducted to improve the learning outcomes of class XI students majoring in Machanical Engineering at SMKN 3 Surabaya in Computer Numerical Control (CNC) subjects which still apply conventional learning, CNC learning basically requires a CNC machine as a supporting medium so that the material presented can increase students attention and interest in learning, therefore this research uses the CNC Simulator Android learning media available at Play Store so that all students can access and own the learning media they will use. The method used is Classroom Action Research, consists of the stages of planning, implementation, observation and reflection. The research was conducted at SMKN 3 Surabaya with the subjects in the research being 29 students. Data collection was carried out using test sheets, in Cycle I using Pre-test and in Cycle II using Posttest. Based on research results and data analysis, it shows that developments have occurred using the learning model project-based learning assisted by the CNC simulator application in CNC subjects. This learning model makes the learning process more varied and enjoyable for students.